Diagnostic of The Biomedical Research in Perú - Chabés y Suárez, Alvaro (1997)
This is an inquiry study about the main issues of the biomedical scientific-technologic progress in Peru. It was made in the view of the comprehensive development of the country, as well as regional and worldwide situation. Health models used to approach socioeconomic inequalities are commented.Positive association between the principal science and technology agency, health field and Pan American health Organization is examined. This is investigated with dyadic evaluations domestic decisions.This article focus scientific and bibliographic attitude, as well as human resources and science and technology investment. In the same way, it outlines a strength and weakness analysis.Strengthen the information and communication necessity to excellence degrees and construction of a new biomedical research culture is noted.The importance of introduce a national progressive accreditation system, suitable human resources, science production with suitable standards and greater aggressiveness in the use of foreign cooperation are focussed.